Quality Control Analysis of Steel Plates Products at PT. ABC Using Seven Tools and Kaizen Method - Sumiati; Isna Nugraha (Future Science, 2022)
Quality is the overall set of characteristics of a product or service in satisfying part or all of the needs of consumers. Consumers as product users always compare in choosing or using products so this situation results in the role of quality being increasingly important. The problems faced by PT. ABC is the defect rate that occurs in the production of High Strength Steel Plates, namely in January - September 2017 the defect rate of the High Strength Steel Plates type is 3.28%. This of course greatly affects the efforts of PT. ABC to increase production results or at least reduce the level of defects that occur. The purpose of this research is to find out the factors that cause defects, analyze product defects and analyze the causes for continuous improvement. This can be done using the Kaizen method. This technique uses the basic tools of Seven Tools. The results showed that based on data processing using Seven Tools, it can be seen that the number of defects from the type of defect on the steel plate High Strength Steel Plates during 9 months was wavy defects with a percentage of 26.36%, wrong cut with a percentage of 27.61%, not symmetrical with a percentage of 25.62%, and deep scale with a percentage of 20.39%. The results of the analysis that the cause of wrong cutting defects are caused by human factors that are not careful, lack of concentration, and lack of skill. To overcome this problem, Kaizen or 5S analysis was made. Improvements have been made to the production of High Strength Steel Plates for a period of 9 months, from 3.28% to 2.60% there was a decrease in defects or 0.68%.